QFD Method as A Tool to Support the Implementation of Innovations in MSP - Case Study - Marta JAGUSIAK-KOCIK (Communications of International Proceedings, 2021)
In article an introduction of a formalized design process, Quality Function Deployment (QFD) to a Small and Medium Enterprises was discussed, in order to design and produce an innovative travel cot. The QFD method was developed for large enterprises in order to improve and optimize the design process. QFD is a powerful tool to analyze customer requirements and aspirations and evaluate how well they can be met or surpassed using product attributes. This method works very well in the sector of large organizations. The aim of the article is to determine the degree of additivity to which this approach can be adapted to the requirements of an SME and successfully embedded in such an enterprise in order to promote a cultural change in design thinking. For the analysis presented in the paper, a survey was used, which was carried out in 21 companies from the children's industry. The survey concerned, inter alia, use of the QFD method in a given company and knowledge of its stages. From a group of 21 companies, a company manufacturing children's furniture was selected for a detailed analysis. The result of the analysis was to create a quality house for a product such as a travel cot and to learn about the relationships that exist between the customer's attributes and technical requirements, as well as between individual attributes. The ease of use and versatility of this method will help to design the production system in order to optimize and improve it.
Keywords: Small and Medium-Sized Enterprises; Quality; Quality Management; QFD Method.